THE PREVALENCE OF PSYCHOSOMATIC DISORDERS AMONG ADOLESCENT SCHOOL GIRLS IN KHARTOUM STATE –SUDAN - Ali Abuzied, Nadia Mahmoud (International Journal of Research -GRANTHAALAYAH, 2019)
Psychosomatic health of adolescent girls at crossroads of childhood and mature adulthood, may lead to various health problems in future. To measure the prevalence and identify factors associated with psychiatric morbidity & psychosomatic symptoms among adolescent secondary school girls in Khartoum. This ‘Study’ was conducted, in three secondary schools of Khartoum North. The Simple Random Sampling Technique was applied to select three schools from the spot map of Khartoum North for this study, and 491 girl students in the adolescent age group were selected from the completed updated list of students from the enrollment registers in these schools. according to the cut-off point (≥ 24 in the G.H.Q -28) findings showed that the prevalence of psychiatric morbidity (severe depression and anxiety) was 60.89% among the adolescent secondary school girls while the psychosomatic disorder was 34.62%. The psychosomatic disorder was found to be significant (P<0.05) with the following three factors: a) late (18-19 yrs.) adolescent age, (61.30%), chi- square= 18.611, df=1, O.R=0.435617 ,CI95%=(0.276629, 0.685981) ; b) physicals abuse (39%) chi- square= 22.34, df =1, O.R=0.281,CI95%=(0.172871, 0.458281) and c) verbal abuse (72%) chi- square= 21.86, df=1, O.R=0.433,CI95%=(0.27331, 0.688). A borderline significant was seen with the family moderate (40%) and low income (40%), chi- square= 5.09, df=2, O.R=(0.839, 0.799),CI95%=((0.508247, 0.503899),( 1.755645 , 1.426668)). However, no significance was there in relation to marital status (married 83.5%), chi- square= 2.324,df=1, O.R=1.06 ,CI95%=(0.586947, 2.197218),mother education (elementary 61.76%) chi square=1.692,df=2,O.R=(1,0.951),CI95%=((0.385528,0.554214),(2.674766, 1.626457)) and further education (high level 73 %) chi- square= 3.17, df=2, O.R=(1.282, 1.024),CI95%=((0.354603, 0.55087,)( 4.49567, 1.903074)). Despite the fact that there is no significant (P>0.05) relation between the fathers' level of education and the occurrence of psychosomatic however, the odds ratio of disease is 28% higher among the girls whose fathers were illiterate in comparison to the girls whose fathers were of high level of education. among adolescent school girls.